A pilot study to explore the effect of udenafil on cerebral hemodynamics in older adults - Qi Wang; Byoung‐Soo Shin; Sun‐Young Oh; Yu Seob Shin; Duk L. Na; Ko Woon Kim (Annals of Clinical and Translational Neurology, 2023)
Abstract Objective Phosphodiesterase‐5 inhibitors (PDE5Is) enhance vasodilation. We investigated the effects of PDE5I on cerebral hemodynamics during cognitive tasks using functional near‐infrared spectroscopy (fNIRS). Methods This study used a crossover design. Twelve cognitively healthy men participants (mean age, 59 ± 3 years; range, 55–65 years) were recruited and randomly assigned to the experimental or control arm, then the experimental and control arm were exchanged after 1 week. Udenafil 100 mg was administered to participants in the experimental arm once daily for 3 days. We measured the fNIRS signal during the resting state and four cognitive tasks three times for each participant: at baseline, in the experimental arm, and in the control arm. Results Behavioral data did not show a significant difference between the experimental and control arms. The fNIRS signal showed significant decreases in the experimental arm compared to the control arm during several cognitive tests: verbal fluency test (left dorsolateral prefrontal cortex, T = −3.02, p = 0.014; left frontopolar cortex, T = −4.37, p = 0.002; right dorsolateral prefrontal cortex, T = −2.59, p = 0.027), Korean‐color word Stroop test (left orbitofrontal cortex, T = −3.61, p = 0.009), and social event memory test (left dorsolateral prefrontal cortex, T = −2.35, p = 0.043; left frontopolar cortex, T = −3.35, p = 0.01). Interpretation Our results showed a paradoxical effect of udenafil on cerebral hemodynamics in older adults. This contradicts our hypothesis, but it suggests that fNIRS is sensitive to changes in cerebral hemodynamics in response to PDE5Is.